"Fame Is Not Just for the Fellas" : Female Renown and the Childhood of Famous Americans Series - Pfitzer, Gregory M. (Book collections on Project MUSE., 2022)
"Between 1932 and 1958, thousands of children read volumes in the book series Childhood of Famous Americans. With colorful cover art and compelling-and often highly fictionalized-narrative storylines, these biographies celebrated the national virtues and achievements of famous women like Betsy Ross, Louisa May Alcott, and Amelia Earhart. Employing deep archival research, Gregory M. Pfitzer examines the editorial and production choices of the publisher and considers the influence of the series on readers and American culture more broadly. In telling the story of how female subjects were chosen and what went into writing these histories for young female readers of the time, Pfitzer illustrates how these books shaped children's thinking and historical imaginations around girlhood using tales from the past. Utilizing documented conversations and disagreements among authors, editors, readers, reviewers, and sales agents at Bobbs-Merrill, "Fame Is Not Just for the Fellas" places the series in the context of national debates around fame, gender, historical memory, and portrayals of children and childhood for a young reading public-charged debates that continue to this day"--